Formulasi Dan Optimasi Sediaan Gel Ekstrak Etanol Kol Ungu (Brassica oleracea L. Var. Capitata F. Rubra) dengan Basis Carbomer - pratama, nofran putra; Kurniawati, Endah; Oktapiya, Tira Risa; Rahmawati, Zerli; Wulandari, Septi (UNIB PRESS, 2024)
Purple cabbage (Brassica oleracea L. Var. Capitata F. Rubra) is known to have anti-inflammatory activity, so it can be used as a medicine to treat inflammation, especially in breastfeeding mothers. To make it easier to use, it is made into a gel formulation. One of the compounds in purple cabbage is anthocyanin which is in the form of glycosides bound to sugar molecules (cyanidin-3 diglucoside-5-glucoside). These compounds have important effects on the body, one of which is anti-inflammatory. To make it easier to use, it is made into a gel formulation. One of the bases used in the formulation of gels is carbomer. Carbomer has better characteristic in terms of the release of active substances compared to other gel bases. The purpose of this study was to make a gel formulation and to determine the effect of purple cabbage extract gel characteristic on the stability of the physical properties of the preparation. The gel was made using a carbomer base with various extract concentrations of 2.5%, 5% and 7.5%. The gel was tested for its physical characteristic including organoleptic, viscosity, pH, dispersionfor 21 days as well as a preference test. The analytical method used is ANOVA with a 95% confidence level and a Likert scale as a comparative test for the formulation based on the respondents' preferences. The results of the gel formulation using a carbomer base with variations in the concentration of the extract showed that the physical characteristic test of all variables showed that all the formulas met the requirements of the physical preparation, namely homogeneous, viscosity with a value below 50,000 cps, a suitable pH of less than 6, and dispersion in line with the viscosity value. The results of the preference test showed that F2 had the best acceptance and many respondents chose it. The conclusion of this study is that all formulas show results that are in accordance with the requirements of the gel preparation. The difference in extract concentration did not show a significant difference to the length of storage time